2015
DOI: 10.1099/jmm.0.000024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antifungal susceptibility of 186 Candida isolates from vulvovaginal candidiasis in southern China

Abstract: There is limited information regarding the molecular epidemiology and antifungal susceptibilities of Candida isolates using the Neo-Sensitabs method in patients with vulvovaginal candidiasis (VVC). From August 2012 to March 2013, 301 non-pregnant patients aged 18-50 years with suspected VVC were prospectively screened at a teaching hospital in southern China. The vaginal isolates were identified by DNA sequencing of internal transcribed spacer and the D1/D2 domain. Antifungal susceptibility testing of seven an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
(28 reference statements)
9
16
1
Order By: Relevance
“…Moreover, C. dubliniensis is almost indistinguishable from C. albicans using this methodology, possibly leading to low reported rates of C. dubliniensis as an etiological agent of VVC (35). That said, molecular diagnostics (e.g., PCR) to distinguish Candida species largely report findings similar to those of culture-based identification (12,24,36). Thus, imperfect or infrequently used diagnostic tools, selfdiagnosis, and availability of over-the-counter treatment options may contribute to the potentially underreported rate of NAC vaginitis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, C. dubliniensis is almost indistinguishable from C. albicans using this methodology, possibly leading to low reported rates of C. dubliniensis as an etiological agent of VVC (35). That said, molecular diagnostics (e.g., PCR) to distinguish Candida species largely report findings similar to those of culture-based identification (12,24,36). Thus, imperfect or infrequently used diagnostic tools, selfdiagnosis, and availability of over-the-counter treatment options may contribute to the potentially underreported rate of NAC vaginitis.…”
Section: Discussionmentioning
confidence: 95%
“…In support of this, a clinical study by Dennerstein et al demonstrated that of 44 women presenting with vaginitis-like symptoms and harboring a NAC yeast, 86% reported spontaneous improvement without requiring antifungal intervention (30). On the other hand, the relatively large number (ϳ5% to 10%) of VVC cases universally caused by C. glabrata cannot be denied, suggesting that NAC species do actively contribute to symptomatic VVC (20,23,24,28). C. glabrata remains a formidable clinical challenge, as these infections are largely unresponsive to standard fluconazole therapy, given the intrinsic resistance of C. glabrata to the azole class (54).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6,10 Among the Fluconazole-resistant isolates, mutations in the ERG11 gene among the candida species are responsible for significant differences in their susceptibility to Fluconazole. 11 Secreted Aspartyl Proteinases (SAP) are considered as a potential factor that may affect the virulence of this yeast. Extracellular proteolytic activity of candida species is caused by SAP.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The reported drug resistance to use of clotrimazole is low and while clotrimazole has been the standard treatment offered, newer medication may also be also as effective. 9 Tioconazole being a single dose application administered by the treating doctor not only ensures complete compliance but also is reassuring to the patient and this probably enhances patient acceptability greatly. In addition it has also been reported that gel form provides for a longer contact time of the active component at the desired location, and results in a more efficient use of the active component and improved effectiveness Gel formulations generally provide faster drug release as compared to ointments and creams and may be useful when available.…”
Section: Discussionmentioning
confidence: 99%